CRITICAL THINKING: A PRIMER FOR CHEMISTRY TEACHERS AND ACADEMICS - TIMOFTE, Roxana S. (2018)
The aim of writing this book was to offer a support to Chemistry teachers andacademics in their endeavors to foster students’ critical thinking. Thetheoretical information was presented in an accessible way, while the focuswas on offering models for learning objectives, class activities and evaluationmethods.